Three essays on financial integration and trade liberalization - Le, Huong, author; Vasudevan, Ramaa, advisor; Bernasek, Alexandra, committee member; Braunstein, Elissa, committee member; Koontz, Stephen, committee member (Colorado State University. Libraries, 2018)
This dissertation is composed of three essays which examine the impact of financial integration and trade liberalization. Chapter I investigates the effect of financial openness on labor share of income by using four measures of the labor share of income: one unadjusted and three adjusted measures of income share which account for earnings from the self-employed workers. The author also uses both measures of capital account openness: de jure and de facto indicators. The empirical work is applied for a panel dataset of 30 countries during the period of 1970 – 2013. Despite using different measurement methods of the labor share of income and financial openness, the results from all specifications support the hypothesis that financial integration leads to a decline in the labor share of income for the all countries sample. Chapter II examines the macro-economic performance of Vietnam through the six phases of Doi Moi reform, and analyzes the impact of external liberalization on economic growth, aggregate demand, employment and income distribution. The decomposition of aggregate demand suggests that private investment was the most important determinant of Vietnamese economic growth during the period of 1994 – 2011, while government expenditure has become more significant since 2005, and the external sector together with government expenditure are the important driving factors of Vietnamese economic growth since 2012. The decomposition of overall labor productivity highlighted the fact that sectoral productivity growth of the service sector plays an important role in the improvement of overall labor productivity in Vietnam. Chapter III aims to investigate the impacts of external liberalization on Vietnamese economic growth and industrial performance at both regional and provincial levels. To this end, the author reviews regional and provincial economic and industrial performance in Vietnam during the period of vigorous reforms of the Doi Moi and external liberalization (1995-2015). The paper employs the fixed effect regression to test the relation of economic growth, industrial performance and trade liberalization at both regional and provincial levels. The estimation results suggest that FDI has positive and strongly significant impact on economic growth of five economic regions: The Red River Delta, Northern midlands and mountain areas, North Central area and Central Coastal area, South East and Mekong River Delta. The study suggests that FDI inflows and trade openness play very important role in accelerating economic growth and industrial performance at both the regional and provincial levels in Vietnam. Regions and provinces with better infrastructure seem to get more benefit from FDI and trade openness, which suggests that provincial authorities should invest in building new and more modern infrastructure and also formulating rules and regulations governing FDI inflows.